2014
DOI: 10.1136/emermed-2014-203770
|View full text |Cite
|
Sign up to set email alerts
|

Interventions targeting the elderly population to reduce emergency department utilisation: a literature review

Abstract: The investigated interventions have mixed effectiveness. Our findings suggest the hospital-based interventions have relatively poorer effects, and should be better connected to the community-based strategies. Interventions seem to achieve the most success with integration of multi-layered elements, especially when incorporating key elements such as a nurse-led multidisciplinary team, integrated social care, and strong linkages to the longer-term primary and community care. Notwithstanding limitations in genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
(109 reference statements)
0
25
0
Order By: Relevance
“…Then, we evaluated the factors associated with URV risk for non-admitted patients and hospitalized patients by using simple variables at the disposal of the emergency care provider. Two models for predicting risk of readmission after hospital discharge using easily available clinical and administrative data have been previously proposed [ 24 26 ], but only half of all discharged patients eventually readmitted were correctly identified [ 22 , 31 , 32 ]. The value of carrying out a geriatric clinical assessment (GCA) and various geriatric scores has been suggested; however most authors agree that this geriatric expertise takes too much time to be performed routinely in ED [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we evaluated the factors associated with URV risk for non-admitted patients and hospitalized patients by using simple variables at the disposal of the emergency care provider. Two models for predicting risk of readmission after hospital discharge using easily available clinical and administrative data have been previously proposed [ 24 26 ], but only half of all discharged patients eventually readmitted were correctly identified [ 22 , 31 , 32 ]. The value of carrying out a geriatric clinical assessment (GCA) and various geriatric scores has been suggested; however most authors agree that this geriatric expertise takes too much time to be performed routinely in ED [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…All elderly patients seen in the ED were included. Even if +65 years old is currently accepted as elderly people by WHO, previous studies on interventions targeting the elderly population to reduce ED utilization in developed countries have been included patients aged greater than 55, 60, 65, 70 and 75 years old [ 22 ]. As 75 years old is the currently accepted value in France to define geriatrics patients, elderly population was defined as patients aged 75-years and over.…”
Section: Methodsmentioning
confidence: 99%
“…These approaches encompass measures to improve the availability of primary or community care so that patients otherwise require hospital transfers could be alternatively cared at their residencies or in the community, and measures of fast tracking and early discharge planning for patients visiting hospitals so that they could depart from the ED or hospital at an earliest time. A large literature has been establishing the possibility of such measures toward reductions in hospital attendances and decrease in length of hospital stays [ 28 , 29 ], both of which would bring about savings in acute hospital service utilisation and thus related costs. Associated savings in hospital care service utilisation are considered as a fundamental driver of the cost-saving potential of such programs; and by this means, hospital resources can be more appropriately and efficiently used by other people in needs.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of ED interventions were organised into four evidence clusters: discharge intervention reviews (11,15,18,19,21), staff-focused reviews (13,14,17,20,23), population focused reviews (22,24), and intervention component reviews (12,16,24). Only 5 of the 15 reviews reported interventions delivered wholly within the ED -the remainder were continued into other settings.…”
Section: Intervention Classificationmentioning
confidence: 99%